1994
DOI: 10.1099/0022-1317-75-11-3185
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Local and Systemic Symptom Determinants of Cucumber Mosaic Cucumovirus in Tobacco

Abstract: Cucumber mosaic cucumovirus (CMV) can be divided into two subgroups, I and II. LS-CMV and most other subgroup II strains cause a mild, systemic mottle on tobacco and can induce a necrotic etching (necrotic rings) symptom on inoculated tobacco leaves. In contrast, Fny-CMV and most other subgroup I strains cause severe, systemic mosaic symptoms on tobacco, but do not induce the necrotic etching symptom. Fulllength cDNA clones of all three genomic RNAs of LS-CMV were constructed and infectious RNAs were generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 14 publications
3
87
0
3
Order By: Relevance
“…2a) could be used to differentiate subgroup I strains (severe symptoms) from subgroup II strains (mild symptoms), similar to the observations of CMV strains systemically infecting tobacco (Zhang et al 1994). Using pseudorecombinants, these authors concluded that CMV RNAs 1 and 2 were involved in determining symptom severity.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…2a) could be used to differentiate subgroup I strains (severe symptoms) from subgroup II strains (mild symptoms), similar to the observations of CMV strains systemically infecting tobacco (Zhang et al 1994). Using pseudorecombinants, these authors concluded that CMV RNAs 1 and 2 were involved in determining symptom severity.…”
Section: Discussionsupporting
confidence: 55%
“…Maize appears to be resistant to systemic infection by most subgroup II strains (Wahyuni et al 1992;Carrère et al 1999;Ryu et al 1998). CMV sequences that control symptom type and virulence have been mapped to the 3a and CP genes on RNA 3 (Carrère et al 1999;Suzuki et al 1995;Sugiyama et al 2000;Szilassy et al 1999), but RNAs 1 and 2 have also been implicated (Roossinck and Palukaitis 1990;Zhang et al 1994;Hellwald et al 2000b;Soards et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the host and virus strain, CMV is known to cause variable symptoms, including necrotic or chlorotic lesions, mild to severe mosaic, stunting, leaf deformation and shoestring formation [14]. Subgroup I strains shows severity in terms of symptom and disease development on tobacco [55]. The present isolate (CMV-SG) induced chlorotic lesions becoming necrotic in local lesion assay host, Chenopodium quinoa 3 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of cDNA clones, which contained either the wild-type (wt) 3a gene and the CP gene replaced by the gene encoding the GFP (pL:3a/GFP), or just the 3a gene replaced by the gene encoding the GFP (pF:GFP/CP), was described previously (Canto et al, 1997). RNA transcripts from any of the above plasmids were generated using T7 RNA polymerase, as described previously (Zhang et al, 1994).…”
Section: Methodsmentioning
confidence: 99%